Ad Petram unde excisi sumus: memoria, estudio y espiritualidad observante en el siglo XV = Ad Petram unde excisi sumus : Memory, study and observant spirituality in the 15th century - Gómez-Chacón, Diana Lucía ca. 21. Jh. (Hispania sacra, 2020)
At the end of the Middle Ages, due to the spiritual crisis, religious orders initiated a complex reform process based on the emulation of their respective founders and spiritual fathers’ charism, in which images played a key role. The study and the necessity to properly instruct the members of the different religious communities also became a subject of discussion, as some of the artworks conceived in the framework of this reform atmosphere manifest.